Early High-Fat Diet Exposure Causes Dysregulation of the Orexin and Dopamine Neuronal Populations in Nonhuman Primates - True, Cadence; Arik, Anam; Lindsley, Sarah; Kirigiti, Melissa; Sullivan, Elinor; Kievit, Paul (Frontiers in Endocrinology, 2018)
Maternal obesity and consumption of a high-fat diet (HFD) during pregnancy has a negative impact on offspring, including an increased risk for the development of obesity in adolescence. The mechanism for this transferred metabolic risk is unclear, but many studies have focused on the brain due to its important role in appetite and body-weight regulation. Two main pathways regulate appetite in the brain; homeostatic regulation that occurs predominantly in hypothalamic circuits and hedonic regulation of feeding that occurs via dopaminergic pathways. The current proposal examined the impact of early HFD exposure on the dopaminergic control of hedonic feeding pathways in a translational nonhuman primate model. Japanese macaque offspring from mothers consuming a control (CTR) or HFD were weaned onto control or HFD at an average 8 months of age yielding four groups: maternal and post-weaning control diet (mCTRpCTR), maternal control diet and post-weaning HFD (mCTRpHFD), maternal HFD and post-weaning control diet (mHFDpCTR) and maternal and post-weaning HFD (mHFDpHFD). Brains from 13-month-old offspring were evaluated for expression of neuropeptides that regulate dopaminergic pathways including orexin, melanin-concentrating hormone (MCH) in the lateral hypothalamus (LH) and tyrosine hydroxylase expression in the ventral tegmental area (VTA). Orexin cell numbers in the LH were significantly increased in animals exposed to a post-weaning HFD, while no difference was observed for orexin mRNA content or MCH cell numbers. Orexin fiber projections to the rostral VTA were significantly reduced in mCTRpHFD, mHFDpCTR and mHFDpHFD groups, but these differences were not significant in the caudal VTA. There was no difference in the percentage of dopamine neurons receiving close appositions from orexin fibers in either the rostral or caudal VTA, nor was there any difference between groups in the number of orexin contacts per TH cell. In conclusion, the current study finds that prolonged early exposure to HFD during the in utero and postnatal period causes alterations at several levels in the dopaminergic circuits regulating reward.